Multifocal osteosarcoma - Phatak, SV; Ghodke, K (Journal of Institute of Medicine Nepal, 2007)
Background: Osteosarcomatosis (also known as multifocal osteosarcoma or multiple sclerotic osteosarcoma) describes a condition in which there are multiple intraosseous foci of osteosarcoma at the time of presentation. Case report: In a patient of multifocal osteosarcoma the simultaneous appearance of multiple skeletal tumors without pulmonary metastatic lesions was seen. However symptomatic lesion was large in comparison to satellite lesions. Case is reported and general subject of multifocal osteosarcoma is reviewed. The full text of this paper is available at Journal of Institute of Medicine website